Photocatalytic Degradation of Ionic Liquid in Wastewater under Visible Light - Ganapathy, Sarvish (Universiti Teknologi PETRONAS, 2016)
Ionic liquids (ILs) have gained its reputation as the green solvent in industry. Due to its characteristics as a good solvent, stable ILs that is discharged into wastewater cannot be degraded easily. Presence of ILs in wastewater is a threat to environment because it has high tendency to act as solvent for other harmful organic compounds that leads to high toxicity.Photocatalytic degradation is a method that has shown remarkable performance in degrading ILs in wastewater treatment. In this project, BmimCl is chosen to be the basis of IL for lab scale photodegradation study using TiO2 photocatalyst. In the present study, TiO2 photocatalyst is synthesized using microemulsion method. Metal/TiO2 is prepared using wet impregnation method whereby the synthesized TiO2 is mixed with desired amount of metal salt.